2014
DOI: 10.1111/papr.12251
|View full text |Cite
|
Sign up to set email alerts
|

Coaching Reduced the Radiation Dose of Pain Physicians by Half during Interventional Procedures

Abstract: The increased use of C-arm fluoroscopy in interventional pain management has led to higher radiation exposure for pain physicians. This study investigated whether or not real-time radiation dose feedback with coaching can reduce the scatter dose received by pain physicians. Firstly, phantom measurements were made to create a scatter dose profile, which visualizes the average scatter radiation for different C-arm positions at 3 levels of height. Secondly, in the clinical part, the radiation dose received by pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…However, procedures with real-time monitoring of the scattered dose profile did not have significantly different exposure levels than procedures without monitoring, presumably because of the shorter procedure time without monitoring. However, real-time coaching on the appropriate position for dose reduction while monitoring the scattered radiation dose increased the physician's awareness of the scattered radiation, reducing the radiation dose to the pain physician by half [ 54 ].…”
Section: Main Bodymentioning
confidence: 99%
“…However, procedures with real-time monitoring of the scattered dose profile did not have significantly different exposure levels than procedures without monitoring, presumably because of the shorter procedure time without monitoring. However, real-time coaching on the appropriate position for dose reduction while monitoring the scattered radiation dose increased the physician's awareness of the scattered radiation, reducing the radiation dose to the pain physician by half [ 54 ].…”
Section: Main Bodymentioning
confidence: 99%
“…Since then, the issue of radiation exposure has been extensively addressed during different types of diagnostic procedures and surgeries, such as in lumbar discography [37][38][39][40], in vertebroplasty [39,40], in kyphoplasty [41], in minimally invasive transforaminal lumbar interbody fusion [42], and in pedicle screw insertion in the lumbar spine [43][44][45]. In pain practice, the radiation levels were explored during lumbar epidural steroid injections [38,[46][47][48][49][50][51][52], in medial branch blocks and facet joint injections [38,[50][51][52][53][54], in intercostal blocks [51], in stellate ganglion blocks [55], and in percutaneous adhesiolysis [51]. [36,[56][57][58], in the eyes [58][59][60], in glands (thyroid, parotid) [58], and in several other tissues (breast, lung, bone, blood) [58,[61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…Two of the 5 physicians in the study routinely used lateral fluoroscopic views, which greatly increase radiation dose and scatter. Interestingly, a 2015 study of interventional pain procedures found that scatter was reduced by 46.4% simply by realtime coaching on ideal physician and C-arm positioning, without any adjustment of radiation dose settings (28).…”
Section: Discussionmentioning
confidence: 99%